Determination of carbamate insecticides in apples, pears, and lettuce by LC with UV detector - Minelli, E. V.; Angioni, A.; Melis, M.; Pirisi, F. M.; Cabras, P. (Aoac International, 1997)
A simple and rapid method was developed for determination of 8 carbamate insecticides and 10 of their metabolites in apples, pears, and lettuce by liquid chromatography with UV diode array detector. With this method no derivatization is needed. Carbamates not belonging to the N-methylcarbamate class and metabolites without the N-methyl group can also be determined.